2017
DOI: 10.1007/s12134-017-0526-0
|View full text |Cite
|
Sign up to set email alerts
|

Deportation and Re-integration: Exploring Challenges Faced by Deportee Residents in the Nkoranza Municipality, Ghana

Abstract: The increase in deportations over the years has had adverse effects on immigrant families, communities, and countries of origin. Involuntary return, especially deportation, causes economic hardship, emotional distress, and family separation. Given the rising number of deportees in Africa and Ghana in particular, this study sought to explore the challenges that confront deportees in re-integrating into the Nkoranza Municipality of Ghana. Using a qualitative research design, 20 participants (19 males and 1 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The bigger research field of post-deportation effects focuses on social, economic and psychological consequences for individuals or communities (e.g. Dako-Gyeke and Kodom, 2017), and for the most part leaves the deportee-receiving state unaddressed. This is despite the fact that deportees may feel a ‘double abandonment’ – by the country that expelled them, but also by their own country, which did not prevent their deportation or support them afterwards (Lecadet, 2012: 156).…”
Section: Deportations Sovereignty and Interests Of Countries Of Originmentioning
confidence: 99%
“…The bigger research field of post-deportation effects focuses on social, economic and psychological consequences for individuals or communities (e.g. Dako-Gyeke and Kodom, 2017), and for the most part leaves the deportee-receiving state unaddressed. This is despite the fact that deportees may feel a ‘double abandonment’ – by the country that expelled them, but also by their own country, which did not prevent their deportation or support them afterwards (Lecadet, 2012: 156).…”
Section: Deportations Sovereignty and Interests Of Countries Of Originmentioning
confidence: 99%
“…62 However, the challenges within the Ghanaian economic system pose tremendous difficulties for returnees who desire to invest their capital gains. 63 The language barrier is identified as one of the key problems that affect the investment of the skills and experience (human capital) Ghanaian returnees acquired in the diaspora. Setrana and Tonah, in examining the post-return experiences of returnees in Ghana, observed that in the context of investing human capital, some skilled returned immigrants in Ghana are challenged with barriers.…”
Section: Difficulties In Investing Capitalmentioning
confidence: 99%
“…This experience can leave long-lasting impacts on them, such as an increase in the incidence of posttraumatic stress disorder (Pena et al, 2017). At the same time, they often face stigma in their local communities, since the reason for deportation is not known by others who are concerned about their potential criminal experience abroad (Wheatley, 2011;Brotherton and Barrios, 2009;Dako-Gyeke and Kodom, 2017). In addition, given that several of them have used their savings (or those of their family network) to afford the costs of migration, they return home poorer and with fewer resources to start over.…”
Section: After the United States Approved The Illegal Immigration Reform And Immigrant Responsibilitymentioning
confidence: 99%